Estimating eligibility for lung cancer screening in an Australian cohort, including the effect of spirometry. Issue 11 (20th June 2016) - Manners, David; Hui, Jennie; Hunter, Michael; James, Alan; Knuiman, Matthew W; McWilliams, Annette; Mulrennan, Siobhain; Musk, Arthur W (Bill); Brims, Fraser JH
Abstract: Objectives: To estimate the proportion of ever‐smokers who are eligible for lung cancer screening in an Australian cohort, and to evaluate the effect of spirometry in defining chronic obstructive pulmonary disease (COPD) when assessing screening eligibility. Design: Cross‐sectional study of 3586 individuals aged 50–68 years who live in the Busselton Shire of Western Australia. Outcomes: Proportion of ever‐smokers eligible for lung cancer screening based on United States Preventive Services Task Force (USPSTF) criteria, and PLCOm2012 lung cancer risk > 1.5%. The effect of using self‐reported COPD, symptoms consistent with COPD, or spirometry to define COPD for screening eligibility according to the PLCOm2012 criteria. Results: Of ever‐smokers aged 55–68 years, 254 (20.1%) would be eligible for screening according to USPSTF criteria; fewer would be eligible according to PLCOm2012 criteria (225, 17.9%; P = 0.004). This is equivalent to 8.9–10.0% of the total population aged 55–68 years, which suggests about 450 000 individuals in Australia may be eligible for lung cancer screening. The proportions of eligible participants were not significantly different whether spirometry results or symptoms consistent with COPD were used to determine PLCOm2012 risk. Conclusions: The proportion of ever‐smokers in this population who were eligible for lung cancer screening was 17.9–20.1%. Using symptoms to define COPD is an appropriate surrogate measure for spirometry when determining the presence of COPD in this population. There are significant challenges for policy makers on how to identify and recruit these eligible individuals from the wider population.